Neoliberalism, P3s, and the Canadian Municipal Water Sector: A Political-Economic Analysis of this "Post-Political" Waterscape - Lang, Michael (Stream: Interdisciplinary Journal of Communication, 2016)
In this paper I consider how the increase of Public-Private Partnerships (P3s) in Canada now threatens the autonomy of municipal water services. P3s have gained traction since the 1990s as a mechanism of private alternative service delivery that replace traditional public provision. Over the past decade, P3s have been actively promoted by the state via quasi-government agencies such as Public-Private Partnerships Canada (PPP Canada), yet their results have been markedly poor. Nevertheless, P3s are now being situated as a key mechanism in the neoliberal (re)regulation of public services, regardless of their shortcomings and inequities. With this in mind, I frame recent Federal policy changes concerning the funding of local water infrastructure and services and their implementation through such agencies as PPP Canada as expressions of post-political governance in Canada. I argue that the capacity for local decision-making concerning this integral social and ecological service is being overwhelmed by a technocratic, expert-driven political process that is contingent on the hegemony of economic austerity to institute municipal water privatization, free from democratic accountability. <!-- [if gte mso 9]> <![endif]--> <!-- [if gte mso 9]> Normal 0 false false false EN-CA JA X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--> <!-- [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Cambria; mso-ansi-language:EN-CA; mso-fareast-language:EN-US;} --> <!--[endif] --> <!--StartFragment--> <!-- [if gte mso 9]> <![endif]--> <!-- [if gte mso 9]> Normal 0 false false false EN-CA JA X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" Priority="51" Name="Grid Table-